Relationship Among Soil Properties And Mycorrhizal Fungi-Liana Association From The Northern Region Of Peninsular Malaysia And The Screening Of Their Phytochemical Properties - Rahim, Norahizah Abd (2022)
The main focus of this study was to determine the presence of association between liana and mycorrhiza. As liana was described by many literatures to have better adaptation during water scarcity season, meanwhile mycorrhiza was known to be helping in nutrient and water uptake of the host it associated with, a hypothesis that there could be a link between these two organisms was made after putting these theories together. Rhizosphere soil and liana samples were collected from Kedah (Gunung Jerai), Penang (Cherok Tokun) and Perak (Royal Belum, Temengor and Teluk Senangin) and the selection of liana were narrowed down to six species: Coscinium fenestratum, Strychnos ignatii, Luvunga crassifolia, Fissistigma manubriatum, Ampelocissus cinnamomea and Smilax sp. Mycorrhizal detection approaches such as spore count and percentage of root infection have been employed to confirm the association of host plant and the fungus thus to further verify hypothesis made. Soil texture and physico-chemical aspects such as soil pH and concentration of nitrogen and phosphorus (soil total, available and shoot) were determined to asses the effects of these elements on the number of spore and root infection.